Does long-term care insurance reduce the disability among middle-aged and older adults? Evidence from China - Na Cao; Tong Shi; Chaoping Pan (BMC, 2023)
Abstract This study aimed to examine whether the implementation of Long-Term Care Insurance (LTCI) policy could reduce the disability among middle-aged and older adults in China, and to test the heterogeneity of the effects. Data came from four waves of the China Health and Retirement Longitudinal Study (CHARLS, 2011 to 2018). The Difference-In-Differences (DID) method and the panel data fixed effect model were used to estimate the effect of implementation of LTCI policy on disability among individuals aged 45 years and above. The LTCI policy had a positive impact on reducing disability among middle-aged and older people. Females, younger adults, city dwellers, and individuals living alone benefited the most from LTCI policy. The results provided empirical evidence for the implementation of LTCI policy in China and other similar countries as China. The implementation of LTCI policy should also pay more attention to inequity of the effects on reducing disability among different demographic groups.